Prototipe “Air Packit” Kotak Penerima Paket Dengan Sensor Barcode Scanner GM66 - Ariep Jaenul; Mauludi Manfaluthy; Noval Prakoso (Universitas Muhammadiyah Ponorogo, 2025)
The development of e-commerce services requires a solution to facilitate the delivery of packages from couriers to users while maintaining package security. This research aims to design an automatic package receiving box using an ESP32 microcontroller as the control unit. The research method uses a prototyping approach through the stages of problem identification, prototype design, implementation, and function testing. The system is equipped with a GM66 sensor to scan barcodes as package validation, a load cell sensor to detect the presence of packages, and a Telegram application as a communication medium with users. The design process includes hardware and software requirements analysis, schematic creation, and draft design. When the system operates, the barcode is scanned by the courier and verified with the receipt number stored in the database, and the locker door will open automatically if the data matches. The test results show that the system functions properly, the GM66 sensor can read the barcode accurately so that the door lock solenoid can open the locker, and the message on the LCD can be read by the courier. This system shows potential in improving security and efficiency of delivery in e-commerce services.